KEPASTIAN HUKUM TERHADAP PERLINDUNGAN HAK ANAK KORBAN PERCERAIAN - Rahmadi Indra Tektona (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
Marriage is one part of the necessities of life that exists in society and also a legitimate institution which is recognized by society and the state. In a marriage relationship, sometimes there will be divorce. Many things may trigger the causes, and usually the victims are children. Rights of children custody often become a problem before or after the divorce. This, becomes the obligations of the parties to protect children's rights.